1980
DOI: 10.1016/0301-6226(80)90105-0
|View full text |Cite
|
Sign up to set email alerts
|

Length of gestation periods of horses and ponies belonging to different breeds

Abstract: The mean gestation periods of mares belonging to different horse and pony breeds common in The Netherlands have been calculated using data from the birth registers of five stud-book societies. The following mean values have been determined: Fjord pony: 342.2; Haflinger pony: 341.3; Draught horse: 343.3; Shetland pony: 337.2; and Frisian horse: 337.7 days. The variation in the mean gestation period is greater in horses than in cows, sheep or pigs. Colts are carried a little longer than fillies. Differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
2

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 5 publications
5
25
2
Order By: Relevance
“…These results differ from the majority of data for different breeds, in which the gestation length for colts was longer than that for fillies (Bos and Van Der Mey, 1980;Davies Morel et al, 2002;Pérez et al, 2003;Valera et al, 2006;Satué et al, 2011a b;Aoki et al, 2012;McCue and Ferris, 2012). Only few publications were not able to detect a significant influence of gender on the length of gestation (Campitelli et al, 1982;Valente et al, 2006), as it was found in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…These results differ from the majority of data for different breeds, in which the gestation length for colts was longer than that for fillies (Bos and Van Der Mey, 1980;Davies Morel et al, 2002;Pérez et al, 2003;Valera et al, 2006;Satué et al, 2011a b;Aoki et al, 2012;McCue and Ferris, 2012). Only few publications were not able to detect a significant influence of gender on the length of gestation (Campitelli et al, 1982;Valente et al, 2006), as it was found in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…We observed longer gestation periods in both younger and older mares ( Table 2). Similar results were obtained in most studies (Akkayan and Demirtel, 1974;Platt, 1979;Bos and Van Der Mey, 1980;Demirci, 1988). This was postulated to be due to a decrease in uterine/placental nutritional efficiency (Pashan and Allen, 1979) and/or the metabolic-hormonal drive to grow (Gluckman and Hanson, 2004), as a consequence of age and the multiparous state, slowing intrauterine growth and prolonging gestation.…”
Section: Influence Of the Maresupporting
confidence: 90%
“…The length of full-term pregnancies varies within a short range of days, even though a certain variability can be appreciated and justified genetically as much as by environmental factors. In horses, the range of variability of the gestation length is larger than in other domestic species (Bos and Van Der Mey, 1980), probably due to the fact that their long gestation period is influenced by physiological factors that do not influence the gestation lengths of other species (for instance, embryonic diapause, reported by Lofstedt, 1992). A number of studies have confirmed these wide variations in gestation length for various breeds of horses (Pérez et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…One factor supporting ruminant radiation into higher latitudes could be that, aside from the giraffids, their gestation periods are below 1 year and can be comparatively short ( cf . the gestation period of domestic cattle at about 278 days compared with that of similar‐sized domestic horses at about 340 days ‐ Jafar, Chapman & Casida, 1950; Bos & Van der Mey, 1980), which makes an adaptation to seasonal environments feasible without loss of a vegetation period for the interbirth interval (Kiltie, 1988). As stated in , the fact that species with gestation periods longer than a seasonal cycle live or lived at higher latitudes indicates that while a short gestation period may be an advantage at higher latitudes, it is not a precondition for expansion into such regions.…”
Section: Discussionmentioning
confidence: 99%